1987
DOI: 10.1677/joe.0.1150233
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic clearance rate of insulin-like growth factor-I in fed and starved sheep

Abstract: The metabolic clearance of insulin-like growth factor-I (IGF-I) has been examined in sheep using a radioiodinated hormone preparation (131I-labelled IGF-I). Following i.v. administration, 131I-labelled IGF-I was distributed in a volume equivalent to plasma (60 ml whole blood/kg liveweight) and demonstrated a triphasic pattern of clearance with apparent half-lives (t 1/2) of 4.0 +/- 0.4 (S.E.M.), 52.4 +/- 3.4 and 792 +/- 26.5 min (n = 10). No significant differences in the t1/2 of the three phases were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
2

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 20 publications
7
47
2
Order By: Relevance
“…Because the small IGFBP complex is believed to facilitate the trans port of IGF-I from serum to tissues, the preferential asso ciation of IGF-I with these IGFBPs in the proteinrestricted animals might allow a faster transcapillary pas sage and distribution to the tissues. In contrast to the stud ies in rats, a 48-hour fasting in sheep did not affect the clearance of IGF-I [37], This difference might be due to species differences or be related to the differences in the nature and length of the nutritional insult.…”
Section: Insulin-like Growth Factor-binding Proteinscontrasting
confidence: 83%
“…Because the small IGFBP complex is believed to facilitate the trans port of IGF-I from serum to tissues, the preferential asso ciation of IGF-I with these IGFBPs in the proteinrestricted animals might allow a faster transcapillary pas sage and distribution to the tissues. In contrast to the stud ies in rats, a 48-hour fasting in sheep did not affect the clearance of IGF-I [37], This difference might be due to species differences or be related to the differences in the nature and length of the nutritional insult.…”
Section: Insulin-like Growth Factor-binding Proteinscontrasting
confidence: 83%
“…Results from other studies suggest that IGF-I clearance from plasma in older sheep does not alter with fasting (Hodgkinson et al 1987). Further, hepatic IGF-I mRNA is reduced in poorly fed lambs (Pell et al 1993).…”
Section: Discussionmentioning
confidence: 80%
“…These studies indicate that nutritionally driven changes in plasma IGF-I in older animals are probably the result of altered hepatic production of IGF-I. IGF clearance rates in sheep of different ages have not been investigated, but a comparison of two independent reports suggests that the metabolic clearance of IGF-I is greater in 6-than 9-month-old wethers (Hodgkinson et al 1987. Also, the clearance rate is greater for IGF-II than IGF-I .…”
Section: Discussionmentioning
confidence: 95%
“…These authors postulated that the dimin ished t./2 in hypox rats was due to a lack of the GHdependent 150-kD IGFBP [7], There have been only two reports of studies in which IGF-I was administered to domestic animal species: Guler et al [8] reported that the t./2 of l25I-IGF-I administered intravenously to mini pigs was 10-15 min for free IGF-I, 20-30 min for IGF-I bound to the 50-kD IGFBP, and 4-6 h for IGF-I bound to the 150-kD IGFBP. More recently, Hodgkinson et al [9] administered 1311-IGF-I (recombinant human) to sheep and found that the label distributed to three phases with ty, values of 4.0 ± 0.4, 52.4 ± 3.4 and 792 ± 26.5 min. Furthermore, these authors provided evidence that the two phases with the longer tiA values were due to IGFBP-bound label.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate interpretation is that exogenous IGF-I is rapidly cleared from the circulation before it can elicit any significant stimulatory effect on proliferation of target cells because it is not bound to IGF-binding proteins (IGFBPs). Previous studies have reported short circulating half-lives of IGF-I injected into rats [7], hu mans [8], and sheep [9].…”
Section: Introductionmentioning
confidence: 92%